Influence Herding and Loss Aversion to Stock Investment Decisions with Fear of Missing Out (FOMO) as a Mediating Variable in the Young Generation in Jakarta - Gita Fitri M Jowey; Ossi Ferli; Erric Wijaya; Enny Haryanti (Greenation Research & Yayasan Global Resarch National, 2024)
This research aims to analyze the influence of loss aversion and herd behavior on stock investment decisions through fear of missing out (FOMO) with the object of young generation investors who are a maximum of 30 years old and domiciled in DKI Jakarta who have carried out stock buying and selling transactions in the last year. Hypothesis testing in this research uses the PLS method or Partial Least Square with software SmartPLS 3.0. The data collection technique uses a questionnaire using the media googleform to collect data from respondents. The results of this research Herding and Loss Aversion does not have a significant effect on investment decisions. Shares of the younger generation of DKI Jakarta are different from the variables Fear of Missing Out which has a significant influence on the stock investment decisions of the younger generation of DKI Jakarta. Herding and Loss Aversion significant effect on Fear of Missing Out young generation of DKI Jakarta. For mediating variables, results can be drawn, namely for Herd Behavior has a significant influence on the Stock Investment Decisions of the younger generation of DKI Jakarta through Fear of Missing Out whereas for. Loss Aversion No has a significant influence on the Stock Investment Decisions of the younger generation of DKI Jakarta through Fear of Missing Out.